2018
DOI: 10.12688/wellcomeopenres.12942.2
|View full text |Cite
|
Sign up to set email alerts
|

Water source most suitable for rearing a sensitive malaria vector, Anopheles funestus in the laboratory

Abstract: The insecticide susceptibility status of one Background:Anopheles funestus, of the main malaria vectors in the Afrotropical regions, remains under-studied due to the difficulty of working with this mosquito species. Collecting their larvae in natural breeding sites, rearing and maintaining them in normal laboratory conditions have been a difficult task. Forced-egg laying technique has been a very good tool to generate eggs from adult mosquitoes collected from the wild but rearing these eggs to obtain satisfyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 25 publications
4
17
0
Order By: Relevance
“…Previous studies investigating the impact of different water sources used for larval rearing in an An. funestus colony (FUMOZ) indicated that their egg hatching rate can exceed 70% [59,60]; con rming hatch rates in this study were low. It is known that females of other Anopheles species can produce unviable eggs without successful mating, or after mating with sperm-less males [61].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Previous studies investigating the impact of different water sources used for larval rearing in an An. funestus colony (FUMOZ) indicated that their egg hatching rate can exceed 70% [59,60]; con rming hatch rates in this study were low. It is known that females of other Anopheles species can produce unviable eggs without successful mating, or after mating with sperm-less males [61].…”
Section: Discussionsupporting
confidence: 68%
“…The larval development period of F 1 -FUTAZ (11-14 days) was similar to that reported for An. funestus in other laboratory settings [59,60,62], but faster than FUMOZ development period (21-23 days) observed in this study. The duration of larval development in An.…”
Section: Discussionsupporting
confidence: 42%
“…Our study represents an initial step in filling this knowledge gap and provides further details regarding the dynamics of changes in both the internal and cuticle surface microbial niches. The homogeneity in internal microbiota of F1 adults is suggestive of a loss in field-acquired microbiota, which could pose an additional set of challenges for field or semi-field mosquito microbiome studiesparticularly studies that rely on laboratory progeny in lieu of field populations to circumvent the challenges involved [25,27,28] in obtaining sufficient numbers of wild mosquitoes of uniform physiological characteristics. Previous findings showed that rearing mosquitoes in water from the field could preserve the field-derived internal microbiota in laboratory-colonized adult progeny of An.…”
Section: Discussionmentioning
confidence: 99%
“…gambiae, breed in sites that are small, temporary and often difficult to find and/or access [22][23][24][25][26], making it hard to obtain sufficient immature field mosquitoes for experiments. Where larval habitats are plentiful and easy to find and/or access, the subsequent rearing of field-collected mosquitoes to obtain uniform characteristics can pose additional challenges [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, nitrate concentrations were higher from day 4 in NCZ compared to NC, indicating greater ammonia conversion to the less toxic nitrate [31]. The cause of overall higher mortality in Anopheles larval trays without-waterchange (NC and NCZ) in comparison to those with water-change (DC and DCZ) could range from hypoxia, ammonia toxicity, inability to transport oxygen, pathogenicity, nutrient enrichment, and competition for food resource [30,[32][33][34]. In addition, the bacterial build-up that typically accompanies waste accumulation could compound these effects, by increasing hypoxia, ammonia production and/or potential direct bacterial toxicity [29,[35][36][37].…”
Section: Discussionmentioning
confidence: 99%